DETERMINAN PERTUMBUHAN EKONOMI HIJAU PADA SEKTOR UMKM INDONESIA TAHUN 2020-2025 - Chrestiana Aponno; Septina Louisa Siahaya (P3M Politeknik Negeri Ambon, 2026)
MSMEs contribute 61% to national GDP but generated 216 million tons of CO₂ in 2022, creating urgency for green economic transformation. This study aims to analyze the influence of green innovation, digitalization, and human capital on green economic growth of Indonesian MSMEs during 2020-2025. Employing a quantitative approach with survey method on 350 MSME practitioners across 15 provinces, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results demonstrate all three variables significantly influence with 62.7% model predictive power. Digitalization emerges as the strongest predictor (path coefficient 0.389; medium-large effect size), followed by green innovation (0.342; medium effect size) and human capital (0.256; small-medium effect size). The model exhibits excellent quality with positive predictive relevance (Q²=0.453) without multicollinearity. Government should design comprehensive policies integrating fiscal incentives, digitalization subsidies, and sustainable vocational training programs. Financial institutions must expand digital-based green financing with transparent ESG monitoring. Future research needs to explore moderating variables and develop longitudinal models for comprehensive understanding of Indonesian MSMEs' green economic transformation.Keywords: Digitalization, Green Economy, Green Innovation, Human Capital, MSMEs